Ozone improved the wound healing in type 2 diabetics via down-regulation of IL- 8, 10 and induction of FGFR expression - Teplyakova, Olga; Vinnik, Yurii; Drobushevskaya, Anna; Malinovskaya, Natalia; Kirichenko, Andrey; Ponedelnik, Darya (Acta Biomedica Atenei Parmensis, 2022)
Background and aim: We aimed to investigate the effect of ozonated autohaemotherapy (OA) on the wound healing, serum values of interleukin (IL) - 6, 8, 10, tumor necrosis factor-alpha (TNF-α), basic fibroblast growth factor (bFGF) and local expression of fibroblast growth factor receptors (FGFR) in type 2 diabetics with the acute soft-tissue infections. Methods: Patients in the first cohort (n-30) received a basic comprehensive treatment (BCT-group), and the second (n=28) also received OA (OA-group). Blood samples for ELISA and tissue specimens for the immunohistochemical examinations were collected at admission (day 0) and at the 9th day of inpatient treatment. Results: The additional using of OA has accelerated the timing of a single and the complete wound granulation and the timing to marginal epithelization, compared with the results of the standard treatment. The use of OA has significantly reduced the production of IL-8, 10 at 9th day. OA-group patients were characterized by consistently high levels of bFGF production in contrast to the BCT-group, where the decreasing in the serum bFGF level was observed. The maximum number of bFGFR - immunopositive labels was observed in OA-group out to 9th day (319,45 (249,90-348,43) versus baseline 192,65 (171,93-207,72), versus BCT-group 123,30 (105,23- 141,10), p<0,001). Conclusions: Application of OA in the complex treatment of the acute soft-tissue infections in diabetics makes it possible to achieve the significant reductions in the duration of the wound inflammation and regeneration phases by eliminating of overproduction of IL- 8, 10 and induction of expression of bFGF and its receptors.